Eksplorasi Tumbuhan Obat di Kawasan Hutan Alam Girimanik Setren Kecamatan Slogohimo Wonogiri - Nela Annofi Kusuma; Titik Suryani (Universitas Sebelas Maret, 2017)
Natural Forest Girimanik one of the forests have flora diversity including medicinal plants. The purpose of this study was to determine the species of medicinal plants at an altitude of 1400-1600 asl. in the Girimanik Natural Forest area. This research method used purposive sampling exploration and method of plotless transect. The results showed that there are 10 orders, 10 families (Umbeliferae, Poaceae, Rubiaceae, Verbenaceae, Papilionaceae, Polygalaceae, Malvaceae, Compositae, Melastomaceae, and Woodsiaceae), 17 genera covering 17 species of medicinal plants spread at an altitude 1400 -1600 asl. The types of medicinal plants found are Centella asiatica, Paspalum scrobiculatum, Ischaemum timorense, Sporobolus poiretii, Stachytarpheta jamaicensis, Diplazium sibiricum, Axonopus compressus, Urena lobata, Melastoma sp., Oplismenus burmanni, Bidens pilosa, Polygala paniculata, Borreria alata, Centrosema molle, Eupatorium riparium, Lantana camara, and Imperata cylindrica.